Effects of sintering temperature on the microstructure and properties of a W-Cu pseudo-alloy - Lebedev, Mikhail; Promakhov, Vladimir V.; Schulz, Nikita; Vorozhtsov, Alexander B.; Lerner, Marat I. (Metals)
This paper studies the feasibility of fabricating pseudo-alloys based on a W-Cu system through vacuum sintering of spherical bimetallic particles synthesized using the electric explosion of copper–tungsten wires in argon. The effects of the sintering temperature on the structure and hardness of the fabricated composites was studied. In terms of the structure of the samples, tungsten particles of predominantly spherical shapes with sizes ranging from submicrons to 80–90 μm were uniformly distributed throughout the copper matrix. Based on the analysis, the volume fractions of tungsten and copper were approximately equal. The calculated average phase compositions for all the samples were 58.9 wt% for W, 27.3 wt% for Cu, and 13.8 wt% WO2. When the annealing temperature increased from 1100 °C to 1250 °C, the wetting of tungsten by molten copper improved, which resulted in the porosity of the copper matrix being at the minimum, as observed in the contact zone. Due to good wetting and a decrease in the viscosity of copper, rearrangement of the solid phase of the tungsten in the bulk of the composites improved, and the density and hardness of the pseudo-alloy increased. The formation of coarse tungsten grains is caused by the fact that submicron and micron particles are growing in size and merging into agglomerates during the course of liquid-phase sintering, and this happens because of the high surface activity of ultrafine particles. Further research will be devoted to solving the discovered problems.